Are Older Adults Up-to-Date With Cancer Screening and Vaccinations? - Douglas Shenson, MD, MPH, MS; Julie Bolen, PhD, MPH; Laura Seeff, MD; Donald Blackman, PhD; Mary Adams, MPH (Centers for Disease Control and Prevention, 2005)
Introduction Public health organizations in the United States emphasize the importance of providing routine screening for breast cancer, cervical cancer, and colorectal cancer, as well as vaccinations against influenza and pneumococcal disease among older adults. We report a composite measure of adults aged 50 years and older who receive recommended cancer screening services and vaccinations. Methods We analyzed state data from the 2002 Behavioral Risk Factor Surveillance System, which included 105,860 respondents aged 50 and older. We created a composite measure that included colonoscopy or sigmoidoscopy within 10 years or a fecal occult blood test in the past year, an influenza vaccination in the past year, a Papanicolaou test within 3 years for women with an intact cervix, a mammogram, and for adults aged 65 and older, a pneumonia vaccination during their lifetime. We performed separate analyses for four age and sex groups: men aged 50 to 64, women aged 50 to 64, men aged 65 and older, and women aged 65 and older. Results The percentage of each age and sex group that was up-to-date according to our composite measure ranged from 21.1% of women aged 50 to 64 (four tests) to 39.6% of men aged 65 and older (three tests). For each group, results varied by income, education, race/ethnicity, insurance status, and whether the respondent had a personal physician. Conclusion These results suggest the need to improve the delivery of cancer screenings and vaccinations among adults aged 50 and older. We propose continued efforts to measure use of clinical preventive services.